Problems of Handling Narcotics Addicts in Indonesia: An Analysis Between Normative Policy and Empirical Practice - Khair, Muhammad Haikal; Agusmidah, Agusmidah; Harianto, Dedi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The problem of narcotics abuse in Indonesia shows that there is a gap between the normative provisions that require rehabilitation for addicts and the practice of prison punishment that is still dominant. This study aims to analyze the implementation of criminal law policies against narcotics addicts through a progressive legal perspective and assess the application of rehabilitative approaches by law enforcement officials. The types of research used are normative juridical legal research and empirical juridical law. The normative juridical approach is carried out by examining laws and regulations, court decisions, and legal literature related to narcotics policy and progressive legal theory, while the empirical juridical approach is carried out to see the implementation of legal norms in practice. The primary data sources in this study were obtained through interviews with law enforcement officials and correctional institution officers, while secondary data sources included primary legal materials in the form of laws and regulations and court decisions, as well as secondary legal materials in the form of books, scientific journals, and official reports of related institutions. The data collection technique was carried out through literature studies and interviews. The collected data was analyzed using qualitative analysis techniques by comparing normative provisions (das sollen) with their implementation practices (das sein). The results of the study show that the criminal law policy against narcotics addicts has not been effective. Addicts are more often sentenced to prison than directed to rehabilitation, so narcotics inmates are the main contributor to prison overcapacity. Law enforcement officials are still oriented towards punishment, coordination between institutions is not optimal, and rehabilitation facilities are still limited. A progressive legal perspective offers a more humanist approach by placing the addict as a victim of addiction in need of recovery through medical and social rehabilitation.